Anthropogenic Impacts on Meiosis in Plants - Fuchs, Lorenz K.; Jenkins, Glyn; Phillips, Dylan W. (Frontiers in Plant Science, 2018)
As the human population grows and continues to encroach on the natural environment, organisms that form part of such ecosystems are becoming increasingly exposed to exogenous anthropogenic factors capable of changing their meiotic landscape. Meiotic recombination generates much of the genetic variation in sexually reproducing species and is known to be a highly conserved pathway. Environmental stresses, such as variations in temperature, have long been known to change the pattern of recombination in both model and crop plants, but there are other factors capable of causing genome damage, infertility and meiotic abnormalities. Our agrarian expansion and our increasing usage of agrochemicals unintentionally affect plants via groundwater contamination or spray drift; our industrial developments release heavy metals into the environment; pathogens are spread by climate change and a globally mobile population; imperfect waste treatment plants are unable to remove chemical and pharmaceutical residues from sewage leading to the release of xenobiotics, all with potentially deleterious meiotic effects. In this review, we discuss the major classes of exogenous anthropogenic factors known to affect meiosis in plants, namely environmental stresses, agricultural inputs, heavy metals, pharmaceuticals and pathogens. The possible evolutionary fate of plants thrust into their new anthropogenically imposed environments are also considered.